ANKYLOSING SPONDYLITIS IN THE VOLGA BULGARIA - D. I. Abdulganieva; V. A. Spiridonov; A. G. Sitdikov; A. I. Zholobov; I. R. Gazimzyanov; V. S. Baranov; Sh. F. Erdes; M. S. Protopopov; T. Yu. Afanasyeva; A. G. Garifullina (Научно-практическая ревматология)
There is much evidence that ankylosing spondylitis (AS) is a disease that is also much older than early human civilizations and man as a whole. Until now, the Russia's earliest (14th c ntury) archaeological finding of such a patient remains a Volga Bulgaria inhabitant suffering with AS during his life. In the Republic of Tatarstan, at the site of an ancient Bulgar settlement appearing in the early ninth century, archaeologists have discovered an unusual grave: the deceased sitting with his back against the western wall of a tomb pitand having a bronze crosslet under his fingers. According to a historical source, it was the way of burying Christian hierarchs as pastors sitting on the altar and anticipating the great assize during which the destinies of human souls should be ruled. Anthropological analysis showed that the bones belonged to a 35–45-year-old man who was 158–163 cm tall. During the examination of the remains,attention was called to the following features of the spinal structure: ankylosis of the inferior cervical and superior thoracic vertebrae (СV–ThI) and inferior thoracic and lumbar spine (ThIV–LII) predominantly due to ossification of the anterior longitudinal ligament. Facet vertebral joints and costotransverse joints were also ankylosed at the same levels. The man's neck was fixed in a bent-over position with the head down, the chin touching the breast bone – the socalled soliciting posture. By and large, the vertebral changes are characteristic of late (X-ray stage III) spondylitis. Spinal and pelvic photos and X-films are given for demonstration. The studies conducted by historical scientists and forensic medical experts suggest that the found remains are most likely to belong to Christian Theodore nicknamed Jerusaleman, also further known as Holy Theodore philosopher Kamsky (Bulgarian), who was mentioned in the Nikon chronicle in 1323.